Mengenal Ulama Sumatera Utara: Nukman Sulaiman dan Pemikiran Islamnya - Didin Saepudin (JURNAL INDO-ISLAMIKA, 2016)
This article depicts the life and works of Nukman Sulaiman descriptively. He is a Muslim learned man and a teacher who was born on 17 April 1917 in Perbaungan. Perbaungan is a district in Serdang Bedagai in North Sumatera, Indonesia. His parents are H. Abdul Aziz bin H. Sulaiman and Hj. Maimunah binti H. Mohd. Arif.  At his at of 25, Nukman Sulaiman married a woman, Hajjah Siti Radiah binti Ahmad Anjang,  on 14 Syawwal 1361 Higera or 25 Oktober 1942 AD. They live on STM Street or Sukajadi Street, Number 17, Medan.1 Nukman Sulaiman had eleven (11) children. Some of them live in Indonesia, and some other abroad.2 Durin his life, Nukman Sulaiman had a simple ideal; that is, to serve people as much as possible and to die with a good end  (husnul khotimah). In fact, he realized this dream by developing al-Washliyah. Here, Nukman Sulaiman was directly involved in establishing Universitas Al-Washliyah (UNIVA/University of Al-Washliyah), and he had been serving himself as a rector of this university for about seventeen years (1970-1987). By this university, he aimed to generate Muslim learned men (`ulama’) as the heirs of the prophets’ teachings in Islam.